Erratum: Correction: Mobile Apps for Covid-19 Detection and Diagnosis for Future Pandemic Control: Multidimensional Systematic Review (Jmir Mhealth and Uhealth 2024 12 e44406 - Fernandez-Campusano, C (2024)
[This corrects the article DOI: 10.2196/44406.]. ©Mehdi Gheisari, Mustafa Ghaderzadeh, Huxiong Li, Tania Taami, Christian Fernández-Campusano, Hamidreza Sadeghsalehi, Aaqif Afzaal Abbasi. Originally published in JMIR mHealth and uHealth (https://mhealth.jmir.org), 08.04.2024.